PENERIMAAN DIRI PADA KORBAN KEKERASAN SEKSUAL SEKALIGUS PELAKU PEMBUNUHAN - Nurchayati Nurchayati; Dayangku Fanny Padillah (Universitas Negeri Padang, 2022)
Self acceptance is important for children including those who have experienced traumatic events in order to gain inner well being and be able to optimize themselves in the future. This study aims to identify and describe the process of self-acceptance for victims of sexual assault including the perpetrator of infanticide. This study employed a case study qualitative method. The subject in this study is an 18-year-old female student who was a victim of sexual violence as well as a perpetrator of infanticide. Researcher used interview instruments for data collection. Data analysis is performed with thematic analysis. The results of this study show that subjects can accept herself fully at this time. This self-acceptance can be seen from the process that starts from the subject experiencing rejection, depression, anger, to acceptance. The most prominent aspects of self acceptance in the subject is a sense of responsibility with the most dominant supporting factor of self acceptance is the existence of social support from the environment.Penerimaan diri penting bagi perkembangan individu termasuk anak yang mengalami kejadian traumatis agar ia mencapai kesejahteraan dan mampu mengoptimalkan potensi dirinya di masa depan. Penelitian ini bertujuan untuk mengetahui proses penerimaan diri pada korban kekerasan seksual sekaligus pelaku pembunuhan pada bayinya. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Subjek penelitian ini adalah seorang pelajar perempuan korban kekerasan seksual berusia 18 tahun yang berstatus terpidana pembunuhan. Peneliti menggunakan instrumen wawancara untuk pengumpulan data. Analisis data dilakukan dengan analisis tematik. Hasil penelitian ini menunjukkan bahwa subjek dapat menerima dirinya secara penuh saat ini. Penerimaan diri ini terlihat dari proses yang dimulai dari subjek yang mengalami penolakan, depresi, kemarahan hingga penerimaan. Aspek penerimaan diri yang paling menonjol pada diri subjek adalah rasa tanggungjawab sedang faktor yang mendukung proses penerimaan diri adalah dukungan sosial dari lingkungan.